Understanding the Implementation of Telerehabilitation at Pre-Implementation Stage: A Systematic Literature Review - Jafni, TI; Bahari, M; Radman, A; Waidah Ismail (Elsevier Science Bv, 2024)
Despite the increased interest of academic scholar in telerehabilitation implementation, there is a scarcity of studies that provide an up to date comprehensive research on it. This study provides a systematic literature review (SLR) on telerehabilitation implementation research. This review explores the processes involved in telerehabilitation implementation, research themes and the factors that influence the implementation of telerehabilitation at pre-implementation stage. In doing this, all relevant articles in the electronic databases of Scopus, ScienceDirect, PubMed, SAGE and Web of Science that published from 2007 to 2017 were reviewed. The results show that four themes have been paid attention by the researchers' including adoption, benefits, readiness and decision making. The factors in the adoption and readiness were found more dominant than others with seven and six factors respectively. Most of the factors from adoption were in the quality aspects (e.g., system quality, information quality and service quality) while change elements (e.g., attributes of the change, attributes of the change targets) in the readiness. Thus, this study suggests that more research is needed for understanding this complex process of telerehabilitation at pre-implementation in a more holistic manner. (C) 2018 The Authors. Published by Elsevier B.V.